Precipitação de óxido de ferro na superfície da alumina ativada visando a adsorção de íons fluoreto de matrizes aquosas - Morelato, Rafaela Roberta (2024)
The presence of fluoride ions (F-) in the water used for supply, in concentrations between 0.6 and 1.5 mg L-1, is an important tool for preventing cavities. However, high concentrations (>1.5) pose health risks to the population, as they can result in dental and bone fluorosis. The state of Rio Grande do Sul (RS) registers high concentrations of F-, between 2 and 50 mg L-1 in groundwater. RS Ordinance Nº. 10/1999 establishes a maximum permissible limit of 0.8 mg F- L-1 in water supplies. Contamination can originate from anthropogenic and natural sources. Adsorption is a technique known for its low cost and easy operation. For the adsorption of fluoride ions, the material commonly used is activated alumina, however, this material has some limitations that interfere with its performance. The pH of the water must be lower than 6.0 for high levels of fluoride ion removal to be achieved. However, the pH of groundwater varies between 5.5 and 8.5. In this work, the main objective was to produce a composite with different mass concentrations (3.5, 7 and 14%) from the surface modification of alumina activated by iron oxide precipitation (Fe/AA) for water defluoridation. The different concentrations of pure iron oxide (Fe1, Fe2 and Fe3) were characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), cryogenic vibrating sample magnetometer (VSM) and zero charge point (pHpcz). The modified material (Fe1/AA, Fe2/AA and Fe3/AA) was subjected to XRD, FTIR, VSM, pHpcz, transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), surface area (BET), N2 adsorption and desorption and leaching by atomic absorption. An adsorption test was carried out using iron oxides, AA and the modified material to check the removal efficiency and adsorption capacity. The material with the best results was Fe1/AA, which was used to carry out the central composite rotational design (CCRD) for two factors (pH and adsorbent dosage), with response surface methodology, and the results for the adsorbent showed that the composite had fluoride adsorption properties in the pH range of 5 to 8.5, with an ideal pH of 8.5 and the adsorbent dosage defined as ideal for the following experiments was 7.8 g L-1. Subsequently, kinetics and isotherm tests were carried out. The results of the adsorption kinetics tests showed that the best model was the pseudo-second order model with R2 ≥ 0.99. The isotherm model that best matched the experimental results was the LIU model, obtaining a qms of 7.31 mg g-1. Thermodynamic analysis revealed a predominance of chemisorption phenomena and an exothermic process. For interfering ions, the ionic affinity of Fe1/AA was F- > sulphate (SO42-) > nitrate (NO3-) > chloride (Cl-). The results of applying Fe1/AA to real water samples showed that, due to the presence of other ions, there was a decrease in the removal efficiency of fluoride ions. It can be concluded that the Fe1/AA adsorbent has a much higher adsorption capacity compared to pure iron oxide and AA, showing high potential for use in removing fluorides from groundwater.